Penerapan Metode Mendongeng dalam Meningkatkan Kemampuan Bahasa Anak - Latansa Fizo Hafizotun; Nurul Tri Ardhiana (Zuriah : Jurnal Pendidikan Anak Usia Dini, 2022)
This research was conducted with the aim of knowing the application of storytelling methods in improving the language skills of children. The method in this study uses a case study approach and uses a descriptive-qualitative method. While the data collection techniques were carried out by means of observation, interviews and documentation. Data analysis used is domain analysis, taxonomic analysis and componential analysis. The results of this study are the application of storytelling methods to children can build first language skills, create learning communities, and understand children's development.